Pelletized Cu-Ni/CePr5 catalysts for H2 purification via Water Gas Shift reaction. (1st July 2020) - Poggio-Fraccari, E.; Bader, G.; Alemany, Luis; Mariño, F.
Graphical abstract: Highlights: Cu-Ni/ceria/Al2 O3 -spheres catalysts are suitable for a scaling-up process. Impregnation over Al2 O3 spheres improved the redox and textural properties of samples. For the Water Gas Shift reaction conditions used, internal diffusion is rate limiting. Cu addition to Ni catalysts enhanced the selectivity towards Water Gas Shift reaction. Bimetallic catalysts showed a great performance in comparison with literature samples. Abstract: Water Gas Shift (WGS) reaction recently gained attraction as a purifying method to remove CO in H2 stream produced from bio-alcohols reforming for fuel cells applications. In previous works, we tested Cu-Ni samples supported on Pr promoted ceria as catalysts for WGS reaction. However, powder samples are not recommended for a scale-up process and ceria samples lack of cohesive forces to obtain a pellet. Then, supported catalysts can be an interesting alternative to study. In the present work, alumina spheres were impregnated in order to replicate the same chemical formulation of powder-state samples. It was studied the influence in catalytic performance of several textural and catalytic features such as: pellet size, active phase content and distribution, Cu:Ni ratio in bimetallic samples, and contact time. The Cu samples showed a moderate activity and the Ni ones a better performance, but tendency to generate CH4 . For all catalysts, the decrease in the pellet size induced a higher CO conversion, indicating strong mass diffusion effects. Besides, it was observed that small addition of Cu to Ni samples significantly moderated the methanation reaction, but maintaining the activity. The change in active metal content slightly modified the activity and changed the selectivity, in agreement with the characterization techniques results (H2 -TPR and OSC). In summary, the sample with Cu:Ni ratio equal to 1:2 with 1.5 wt%, presented a great performance, by removing 8 to 2 %v/v of CO with an acceptable contact time and high selectivity, being the most promissory catalyst for higher scale tests.